121 The Queen Square tests of auditory cognition: defining hearing deficits and dis- ability in dementia. Issue 6 (27th May 2022) - Johnson, Jeremy; Benhamou, Elia; Sivasathiaseelan, Harri; Requena-Komuro, Mai-Carmen; Nelson, Annabel; Rohrer, Jonathan; Bamiou, Doris-Eva; Hardy, Chris; Warren, Jason
Abstract : Background: Hearing impairment has emerged as a potent association of cognitive decline in dementia and a promising treatment target. To realise this promise, we need to resolve fundamental questions concerning the roles of peripheral versus central auditory deficits in different dementias. Methods: Using a novel psychoacoustic battery – the Queen Square Tests of Auditory Cognition (QSTAC) – we combined pre-existing and novel measures of peripheral and central hearing functions, to charac- terise discrete 'auditory phenotypes' across dementia syndromes. Customised auditory symptom ques- tionnaires (completed by patients' caregivers) were used to capture daily-life hearing-related disability and care burden. Patient groups: Alzheimer's disease, frontotemporal dementia, primary progressive aphasia (PPA) and control. Neuroanatomical associations of specific hearing deficits were assessed using voxel-based morphometry. Results: Syndromic signatures of peripheral and central auditory dysfunction were identified. Alzheimer's disease was associated with prominent impairments of auditory scene analysis and dichotic listening. PPA syndromes and behavioural variant FTD (BvFTD) were principally associated with deficits of sound pattern analysis, sound identity, emotion recognition and degraded speech perception, which stratified according to sub-syndrome (logopoenic, semantic, nonfluent). Conclusions: Taken together, our findings suggest that major dementias have characteristic and differenti- ated auditory phenotypes, reflecting a complex interplay of peripheral hearing and auditory cognitive dysfunction. jeremy.johnson@doctors.org.uk